Studi kesesuaian perairan pantai tanjung setia sebagai kawasan wisata bahari kabupaten lampung barat Provinsi lampung - Aziz, Zulkifli; Subardjo, Petrus; Pratikto, Ibnu (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Faithful Cape Coast is one of Lampung destinations featured attraction and a tourist attraction in West Lampung regency which has considerable potential as a marine tourism area. This study aims to identify and assess physical potential of Cape Coast Faithful as marine tourism area. This study aims to identify and assess physical potential of Cape Coast Faithful as marine tourism area. The results of the study showed that the physical condition of the waters of Cape Coast Faithful potential as marine tourism area, with some activity that is surfing (Surfing), diving (Diving), and fishing (Fishing). Based on the IKW for surfing activities (Surfing) into the category of class S1 (very suitable) with IKW value by 80%, whereas for diving (Diving) and fishing (Fishing) in the category S2 (quite appropriate) with each IKW value of 70% for diving (Diving), and 64% for fishing activities (fishing).